2022
DOI: 10.3390/diagnostics12051222
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Bulk T-Cell Receptor Repertoire Sequencing Analysis in Understanding Immune Responses to COVID-19

Abstract: Measuring immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 19 (COVID-19), can rely on antibodies, reactive T cells and other factors, with T-cell-mediated responses appearing to have greater sensitivity and longevity. Because each T cell carries an essentially unique nucleic acid sequence for its T-cell receptor (TCR), we can interrogate sequence data derived from DNA or RNA to assess aspects of the immune response. This review deals with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 105 publications
(151 reference statements)
0
8
0
Order By: Relevance
“…GLIPH2 algorithm offers an optimal solution. By combining global and motif‐based CDR3 sequence, physiochemical properties, V‐gene bias, CDR3 length bias, and clonal expansion bias, GLIPH2 assesses the antigen‐specific nature of the repertoire and aggregates clonally related TCR sequences or very similar CDR3s, or sequences likely binding the same antigen [34]. Our findings revealed that specificity groups of TCRs in BS provide information about the complexity of an immune response or the presence of a meaningful shared specificity across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…GLIPH2 algorithm offers an optimal solution. By combining global and motif‐based CDR3 sequence, physiochemical properties, V‐gene bias, CDR3 length bias, and clonal expansion bias, GLIPH2 assesses the antigen‐specific nature of the repertoire and aggregates clonally related TCR sequences or very similar CDR3s, or sequences likely binding the same antigen [34]. Our findings revealed that specificity groups of TCRs in BS provide information about the complexity of an immune response or the presence of a meaningful shared specificity across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, viral RNA was sometimes found without the concurrent finding of SARS-CoV-2 virions, and viral mutations were identified throughout various extrapulmonary tissues in patients in whom disease course was prolonged ( 35 ). Regarding TCR clones specific for the SARS-CoV-2 virus, previous studies have utilized TCR repertoire profiling in blood to obtain biological insights into COVID-19 infection ( 36 ), including enrichment of SARS-CoV-2-specific TCRs in the blood of patients with more severe disease ( 37 ). However, local tissue coordination of cellular and humoral immune response against SARS-CoV-2 is critical for developing immunological memory necessary for viral protection, including memory responses, in the periphery ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of gDNA is proportional to the number of analyzed cells with a 1:1 number of clonotypes and number of cells ratio (1 gDNA template per cell), allowing us to determine the relative abundance of sequences in a sample at the cost of unavoidably detecting potentially irrelevant and non-expressed sequences that must be removed through post-processing bioinformatic analysis [ 45 , 46 ].…”
Section: Tcr Repertoire Via Hts: When Details Mattermentioning
confidence: 99%